Analysis of Fume Enrichment Methods and Release Patterns of Plant-Mixed Asphalt Mixtures - Tengfei Nian; Jiaqi Song; Jinggao Li; Ping Li; Xiule Chen (Journal of Highway and Transportation Research and Development)
The disorderly emission and poor treatment effect of asphalt mixture fume in asphalt mixing stations have caused huge harm to the natural environment and human health. Based on the gravimetric method, self-designed and assembled fume generation-enrichment device that was suitable for the mixing state of asphalt mixture in the plant, and conducts research on the fume release rules during asphalt mixture mixing. Four kinds of petroleum asphalt were selected to consider the conditions of asphalt fume generation in the field mixing station. The mixing temperature, aggregate specific surface area and mixing frequency were determined as the key factors affecting the release of fume. The exposed area of the aggregate was calculated by the measured modified specific surface area calculation method, and the influence of each key factor on the smoke release of the plant-mixed asphalt mixture was analyzed. The results show that the self-designed and assembled fume generation-enrichment device has good stability and can ensure the accuracy of the experimental results. The magnitude of the light components in the fume under different mixing conditions is much lower than that of the heavy components, and the fume release after the base asphalt is modified by SBS is reduced. Mixing temperature is the most critical factor that determines the amount of fume release. The amount of fume release shows an obvious growth trend with the increase in temperature. Fume production has strong temperature sensitivity, and release varies significantly under different mixing temperatures. 160 ℃ and 170 ℃ are the jumping nodes of fume release. The amount of fume produced by the asphalt mixture is directly proportional to the specific surface area of the aggregate. The specific surface area of the aggregate directly affects the amount of fume released by determining the exposed area of the asphalt. The amount of fume release is positively related to the mixing frequency. Compared with the heavy components of the fume, the release amount of the light components of the fume is less affected by the mixing frequency. The research results can provide theoretical and technical support for the release and disposal of fume in mixing plants.